Rapid and Sensitive High-Performance Liquid Chromatography/Tandem Mass Spectrometry Method for Determination of Danshensu in Rat Plasma - Jin-qian Wang; Yan ting; Yin-fang Chen; Yue-sheng Wang (Journal of Proteomics and Genomics Research, 2013)
A sensitive, specific and rapid high-performance liquid chromatography/tandem mass spectrometry (hplc–ms/ms) method has been developed and validated for the determination of danshensu (dss) in rat plasma in the present study. The analytes were separated on a c18 column (50 mm×2.1 mm, 1.7 μm) and a triplequadrupole mass spectrometry equipped with electrospray ionization (esi) source was applied for detection. The simple protein precipitation was applied to extract dss from the plasma (about 80%). The method was linear over the concentration ranges of 50–1000 ng/ml for dss. The lower limit of quantitation (lloq) of dss was 50 ng/ml. The intra-day and inter-day relative standard deviation (rsd) were less than 15% and the relative error (re) were all within 15%. Finally, the method was successfully applied to support the pharmacokinetic study after guanxinsu solution was orally administrated to the sprague–dawley rat, respectively.
Keywords: High-Performance Liquid Chromatography/Tandem Mass Spectrometry